Legal Cost Insurance as a Strategic Device - Roland Kirstein (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 1997)
Legal Cost Insurance (LCI) is not only a device to reallocate risk, but also to enhance an insured's position in a settlement negotiation. The paper points out that this function of LCI is especially important in cases that have a negative expected value for potential plaintiffs. Hence LCI is of interest even for risk-neutral customers. – – Rechtsschutzversicherungen (LCI) dienen nicht nur der Risikoallokation, sondern verbessern auch die strategische Position des Versicherten in Vergleichsverhandlungen. Dies gilt insbesondere bei Klagen mit negativem Erwartungswert für den potentiellen Kläger. Dadurch sind LCI sogar für risikoneutrale Kunden interessant.
Keywords: K41; G22; 330; Legal Cost Insurance; Bargaining; Settlement